Avaliação das práticas e conhecimentos de profissionais da atenção primária à saúde sobre vigilância do desenvolvimento infantil Evaluation of practices and knowledge among primary health care professionals in relation to child development surveillance - Amira Consuêlo de Melo Figueiras; Rosana Fiorini Puccini; Edina Mariko Koga da Silva; Márcia Regina Marcondes Pedromônico (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2003)
O objetivo desta pesquisa foi avaliar os conhecimentos e práticas relacionados à vigilância do desenvolvimento da criança de 160 profissionais que atuam na atenção primária à saúde, no Município de Belém, Pará. Foram selecionados 40 médicos e 40 enfermeiros de Unidades Municipais de Saúde (UMS), e 40 médicos e 40 enfermeiros do Programa da Família Saudável (PFS). Na avaliação dos conhecimentos por meio da aplicação de teste objetivo, o percentual de acerto foi de 63,7% para médicos das UMSs, 57,3% para médicos do PFS, 62,1% para os enfermeiros do PFS e 54,3% para enfermeiros das UMSs. Na avaliação das práticas, apenas 21,8% das mães informaram que foram indagadas sobre o desenvolvimento dos seus filhos, 27,6% que o profissional perguntou ou observou o desenvolvimento da sua criança e 14,4% que receberam orientação sobre como estimulá-las. Concluímos que médicos e enfermeiros da atenção primária no Município de Belém apresentam deficiências nos conhecimentos sobre desenvolvimento infantil e que a vigilância do desenvolvimento não é realizada de forma satisfatória, sendo necessárias sensibilização e capacitação dos profissionais para esta prática. In the present study, the practices and knowledge of 40 physicians and 40 nurses from municipal health care units (UMS) and 40 physicians and 40 nurses from the Family Health Program (FHP) in Belém, Pará State, Brazil, all of whom working in primary health care, were evaluated in relation to child development surveillance. Measures of knowledge of child development showed an average of 63.7% correct answers for UMS physicians, 57.3% for FHP physicians, 62.1% for FHP nurses, and 54.3% for UMS nurses. Only 21.8% of mothers attending appointments mentioned that the health care professional had asked about their children's development, 27.6% of mothers reported that the health care professional had asked about or observed the child's development, and 14.4% mothers reported having received instructions on how to stimulate their children's development. According to this study, primary health care physicians and nurses in the municipality of Belém showed gaps in their knowledge of child development. Child development surveillance is not being conducted satisfactorily in primary health care in the municipality of Belém. It is thus necessary to raise the awareness of health care professionals concerning the problem and provide them with appropriate training.